Routledge philosophy guidebook to Rousseau and the social contract - Bertram, Christopher, 1958- (London ; New York : Routledge, 2004)
Rousseau's Social Contract is a benchmark in political philosophy that has inspired and influenced moral and political thought since publication and is widely studied for this reason.
1. Rousseau, the man -- 2. Human nature and moral psychology -- 3. Man is born free (bk. 1, ch. 1-2) -- 4. False theories of the body politic (bk. 1, ch. 3-5) -- 5. The social pact and property (bk. 1, ch. 6-9) -- 6. Sovereignty and the general will (bk. 2, ch. 1-6) -- 7. The lawgiver, culture and morality (bk. 2, ch. 7-12) -- 8. Government and sovereign (bk. 3) -- Civil religion (bk. 4, ch. 8) -- 10. The social contract in retrospect.
Includes bibliographical references (pages 205-209) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Rousseau, Jean-Jacques, -- 1712-1778.; Du contrat social (Rousseau, Jean-Jacques); Rousseau, Jean-Jacques -- 1712-1778.; Rousseau, Jean-Jacques (1712-1778).; Rousseau, Jean-Jacques, -- (1712-1778); Rousseau, Jean-Jacques, -- 1712-1778.; Rousseau, Jean-Jacques, -- 1712-1778.; Rousseau, Jean-Jacques <1712-1778>; Rousseau, Jean-Jacques.; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Essays; Gesellschaftsvertrag; Du contrat social ou Principes du droit politique (Rousseau); Contrat social; État.; Philosophie politique; Théorie politique